PERAN FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN INVESTASI PRODUK MULIA PADA PT. PEGADAIAN (PERSERO) DI KOTA JAMBI - Johannes .; Taufik Daya (DIGEST MARKETING, 2017)
The researchpurposes is to analyze and explain the influence of psychological variables on MULIA product investment. Psychological variables examined consist of motivation, perception, learning, and beliefs and attitudes. The research surveyed of 92 respondents that choosen through PT. Pegadaian customer record. Data analysis use Regression technique. The result shows that simultanly psychological factors have a significant impact on investment decisions of MULIA product. Partially, motivation and perception variables have significanteffecton investment decision.